(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
This work was carried out during the two successive seasons (2012/2013 and 2013/2014) to investigate the effect of different planting locations on quantity and quality of Pelargnium graveolens L. volatile oil. The experiment was conducted at five different locations in Egypt in newly reclaimed lands as follows: North Sinai Governorate (El-Qantara Sharq), El-Monofia Governorate (El-Sadat City), Matrouh Governorate (Siwa Oasis - Khamisa Village), Beni-Suef Governorate (West of Semsta Center) and Giza Governorate (El-Bahariya Oasis - Mandisha Village). Results indicated that all studied parameters such as essential oil percentage, essential oil yield per feddan, essential oil chemical composition and essential oil quality factors (citronellol content, geraniol content and citronellol : geraniol ratio) were affected and varied according to planting location and harvesting time. The best locations for production of geranium oil were El-Qantara Sharq followed by El-Sadat City and then Beni-Suef Governorate locations.